Molecular detection of highly pathogenic avian influenza A (H5N8) virus isolated from domestic ducks and chickens in Egypt across 2018-2021 - Ali, Ahmed A.H.; Soliman, Adel M.; Kotb, Gamelat k.F.; Sewede, Kareem E.; Abdallah, Fatma M. (Journal of Advanced Veterinary Research, 2024)
The present study was carried out to describe Egyptian H5N8 viruses isolated from vaccinated duck and chicken flocks in 2018-2021 from different provinces, Egypt. This study screened 10 vaccinated farms (five duck and five chicken) suffering from respiratory & nervous signs with high mortality rate (90%). Out of ten examined flocks, six flocks were positive for avian influenza virus (AIV) by virus isolation into embryonated chicken eggs (ECEs) for third blind passages. The initially positive samples were confirmed, identified molecularly using quantitative reverse transcriptase-polymerase chain reaction (RT-qPCR) using primers targeting M gene of influenza A. RT-qPCR positive isolates were subjected to partial amplification of hemagglutinin (HA) and neuraminidase (NA) genes using RT-PCR followed by sequencing and phylogenetic analysis for six isolates representative for one duck flock and five chicken flocks. Our findings proven that four flocks only were found positive for AIV/HPAI H5N8 virus by sequencing and phylogenetic analysis for HA and NA genes. The similarity between nucleotide sequencing for the four HA and NA was 99.8% and 98.1%, respectively, with H5N8 viruses previously detected in Russia, Iran, Israel and Iraq. As well as, the phylogenic analyses, focusing on HA and NA genes indicated that Egyptian H5N8 viruses clustered in group B Russian like reassortant H5N8 viruses of clade 2.3.4.4. In conclusion, the detection of the HPAI H5N8 virus in domestic birds even in vaccinated birds is a serious threat; therefore, this is needed for periodic molecular monitoring with vaccine efficacy evaluation and annual surveillance.